An Efficient Electrochemical Approach for the Characterization of Interfacial Strength of Nano Titania-silica Composite Coating on Titanium Implants - Mathai, Suja (Current Advances in Chemistry and Biochemistry Vol. 9, 2021)
The thermal decomposition process developed in the present work is a viable technique for the formation of a nano (TiO2-SiO2) composite coating on Titanium substrate. The electrochemical experiments revealed that the developed coatings had high degradation resistance characteristics and high biomimetic growth characteristics. There was no degradation on the coating even when it was subjected to different extent of electrochemical polarization and anodic current impression. The biomimetic growth studies of these coatings were carried out. The results of elemental analysis of the SBF solution, electrochemical characterization and surface topographical analysis including SEM and AFM carried out at different stages revealed that there was an efficient apatite growth.